Instrumen Gaya Berpikir: Membantu Adaptasi Kognitif dalam Penyelesaian Masalah Fisika - Haeruddin Haeruddin; Jusman Jusman; Nurjannah Nurjannah; Muhammad Zaky (Universitas Tadulako, 2023)
This study aims to develop an instrument to measure thinking styles and their impact on cognitive adaptation in the context of physics problem solving. Understanding how individuals approach and solve physics problems can provide valuable insights into cognitive processes and strategies used. The instrument consists of various tasks designed to depict different thinking styles commonly employed in physics problem solving. These thinking styles include concrete sequential (CS), abstract sequential (AS), concrete random (CR), and abstract random (AR) thinking styles. This research follows the Research and Development (R&D) model. The development model used is the non-test instrument development model. The instrument utilizes a forced-choice model by asking respondents to determine the order of statements that best align with their condition when solving physics problems. The instrument provides four options ranging from very inappropriate to very appropriate. A total of 683 first-year students at Universitas Tadulako participated in the pilot study, and 364 in the implementation study. The expert judgment data analysis technique used the Aiken's formula. Empirical data analysis was conducted using the Ques program to test goodness of fit to the Partial Credit Model (PCM), item validity, and instrument reliability. The content validity result showed an Aiken's V value of .81, and the test reliability was .90. The average infit MNSQ value was 1.00 with a standard deviation of .18. This study found that physics education students at Universitas Tadulako tend to have an abstract sequential (AS) thinking style. The implications of these findings can be utilized to measure students' thinking style tendencies when solving physics problems.